Physical properties and biological activities of hesperetin and naringenin in complex with methylated p-cyclodextrin - Waratchada Sangpheak (2018)
© 2015 Sangpheak et al; licensee Beilstein-Institut. The aim of this work is to improve physical properties and biological activities of the two flavanones hesperetin and naringenin by complexation with β-cyclodextrin (β-CD) and its methylated derivatives (2,6-di-O-methyl-β-cyclodextrin, DM-β-CD and randomly methylated-β-CD, RAMEB). The free energies of inclusion complexes between hesperetin with cyclodextrins (β-CD and DM-β-CD) were theoretically investigated by molecular dynamics simulation. The free energy values obtained suggested a more stable inclusion complex with DM-β-CD. The vdW force is the main guest-host interaction when hesperetin binds with CDs. The phase solubility diagram showed the formation of a soluble complex of ALtype, with higher increase in solubility and stability when hesperetin and naringenin were complexed with RAMEB. Solid complexes were prepared by freeze-drying, and the data from differential scanning calorimetry (DSC) confirmed the formation of inclusion complexes. The data obtained by the dissolution method showed that complexation with RAMEB resulted in a better release of both flavanones to aqueous solution. The flavanones-β-CD/DM-β-CD complexes demonstrated a similar or a slight increase in anti-inflammatory activity and cytotoxicity towards three different cancer cell lines. The overall results suggested that solubilities and bioactivities of both flavanones were increased by complexation with methylated β-CDs.